Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Di Kabupaten Kuantan Singingi Provinsi Riau - Novalia, Lusi; Putro, Tri Sukirno; Sari, Lapeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is done conducted by in Sub-Province Pestle of Singingi as a mean to know factors influencing unemployment storey;level exist in Sub-Province Pestle of Singingi. Data used is data of time series in the form of data of skunder with duration 10 year of year 2003-2012.Uji analysis the used is doubled linear regression by using statistical test of persial test with degree of confidence 95%. To test F in measure with test R² and also by using beta test. Result of research obtain;get conclusion of persial of wage rate variable of minimum (X₁) having an effect on signiflcance to unemployment level. And level of PDRB ( X₂) and also mount opportunity of job/activity (X₃) by persial have an effect on do not significance to unemployment level. biggest variable its influence to unemployment level is Sub-Province minimum wage rate and is smallest of its influence is variable mount opportunity of jobactivity. By together minimum wage rate variable (X₁), mount PDRB ( X₂) and level opportunity of job/activity (X₃) have an effect on do not significance to variable mount unemployment (Y).Keywords: unemployment, minimum wage, PDRB, and Opportunity ofjobactivit